Notes on the occurrence of the Little Curlew in Indonesia - van Balen, Bas (KUKILA, 1996)
The Little Curlew Numenius minutus breeds in the dry, open steppes of northern Siberia and winters in the dry grassy plains of the northern interior of Australia, where they gather in thousands (Pringle 1987). The birds are passage migrants through the eastern part of Indonesia. The largest numbers appear to pass through New Guinea (Beehler et al. 1986; Coates 1985), with very few records either further east (Coates 1985: New Britain and Bougainville) or west of the island The habitat where the birds on passage are encountered in Indonesia resemble the breeding and wintering habitat, and they should be sought in areas of short grass, at airports for example. The status of the species in the area west of New Guinea (Sulawesi, the Moluccas, and Greater and Lesser Sundas) is discussed in this paper.